IMPLEMENTATION OF CAREER GUIDANCE IN IMPROVING CAREER PLANNING SKILLS IN STUDENTS IN SENIOR HIGH SCHOOL - Lika; Mega Iswari; Daharnis (Literasi Nusantara, 2022)
Career guidance is one of the efforts to know and understand himself, or understand what is in the individual well, and to know well the work. Then what is meant by career planning is a process when individuals can identify and take efforts to achieve the goals of their career. Through career planning each individual can evaluate his or her own abilities and interests, consider career opportunities, draw up career goals, and plan practical development activities.